A Case Report of Clozapine-induced Pleural Effusion in a 28-Year-Old Chinese Male. Issue 2 (March 2022) - Wolfe, Christine L.; Hamilton, Joshua; Rogahn, Megan; Brooks, Stephanie; Ahmed, Iqbal
Abstract : Increasing reports have appeared of pleural effusion and peripheral eosinophilia associated with clozapine treatment. These reports describe the onset of pleural effusion from 2 to 5 weeks after initiation of clozapine. Here, we describe a case of a 28-year-old Chinese male who presented with pleural effusion and peripheral eosinophilia ∼17 weeks after initiation of clozapine. We discuss this delayed presentation and examine the potential significance of the patient's East Asian ethnicity. We recommend clinicians consider ethnicity and other factors that can affect the metabolism of clozapine when choosing a clozapine titration schedule and when monitoring during clozapine treatment.